The Effect of Working Capital and Effectiveness of Working Capital on Profitability in Metal and Cement Manufacturing Companies Listed on Indonesia Stock Exchange - Rendi Avinanta Sinuraya (TRIGIN PUBLISHER, 2021)
The objective of this research is to know the influence of working capital and working capital turn over either partially or simultaneously have an effect significantly on profitability of metal and cement manufacturing registered in Indonesia Stock Exchange. The hypothesis of research was that work capital and it's circulation have positive and significant effect on profitability of metal and cement manufacturing registered in the Stock Exchange of Indonesia. This research is classified as causal research with 18 companies from 19 metal and cement manufacturing companies registered in Indonesia Stock Exchange and they maintained complete financial statements that have been audited since 2007-2011 gained from the sites www.idx.co.id and www.icmd.com. Sample was selected by using purposive sampling method. The process of data analyzes used was classic assumption test and hypothetical test. The result of research indicated that work capital and working capital turn over simultaneously have significant effect. Partially working capital has a significant effect on profitability of metal and cement manufacturing registered in the Indonesia Stock Exchange.